Evaluation of Adipose Tissue Hormones and Tumor Necrosis factor in Patients with Endometriosis - Bajilan, Suzan Ibrahim (Journal of Contemporary Medical Sciences, 2024)
Objective: To evaluate levels of physiological parameters (Testosterone, follicle stimulating hormone FSH, luteinizing hormone LH, leptin and tumor necrosis factor TNF-α, Adipsin and Ghrelin), Total antioxidant capacity-TAC, Glutathione S transfers -GST in sera of patients with endometriosis. Method: This study involved (85) women within reproductive age (25-40) years, who were distributed into two groups: patientsʹ group (55) women diagnosed with endometriosis, and (30) healthy control women. The study was carried out at Al-Karkh Maternity Hospital/ Baghdad and extended from 20/4/2024 to 20/5/2024. The pathological cases of patients were diagnosed by clinical examinations and confirmed by specialist physician with ultrasound examination. Blood samples were taken from both groups, serum was separated for each individual by a centrifuge. Results: a significant rise in the (FSH, Leptin, TNF -α, Adipisin) while a significant decrease in levels of (Testosterone , LH, GST, TAC, Ghrelin) concentration were found in the sera of patients compered to healthy women , with a probability of P ≤ 0.05. According to Receiver operating characteristic (ROC) statistical analysis, Area under curve (AUC ) for LH, leptin, TNF -α, adipsin, ghrelin, GST, TAC were closely or equal to (1) for patients . Conclusion: serum levels of LH, Leptin, Adipisin, Gherlin, TNF-α and GST can be dependable as prognostic indicator markers that reflect the degree of oxidative stress accompanying endometriosis.